Effects of altitude on maximum anaerobic power and blood lactate responses - Brands, R. L.; Cooper, T. L.; Leonard, M. J.; Seelbach, J. D.; Davis, J. E. (Medicine & Science in Sports & Exercise, 1998)
This study compared maximum anaerobic power, peak blood lactate, and blood lactate washout times following active and passive recovery at sea level and during acute and chronic hypoxia at moderate altitude (3,400 m). Ss (N = 6) performed two Wingate Anaerobic Power Tests at sea level, at altitude after arrival and after two weeks of residency, and again two days after return to sea level. Active or passive recovery was performed after each test trial in each condition. Maximum anaerobic power and peak blood lactate values decreased significantly from sea level to the second week at altitude. Original sea level values were significantly higher than those measured two days after return from altitude for both factors. Blood lactate washout times were similar for both forms of recovery for all measurement times. Implication: Altitude exposure suppresses blood lactate levels after anaerobic exercise. It is unlikely that altitude training will assist anaerobic exercise performance upon return to sea level.